Statistical Mechancis - Gallavotti, Giovanni; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
C. Cercignani: A sketch of the theory of the Boltzmann equation.- O.E. Lanford: Qualitative and statistical theory of dissipative systems.- E.H. Lieb: many particle Coulomb systems.- B. Tirozzi: Report on renormalization group.- A. Wehrl: Basic properties of entropy in quantum mechanics.
C. Cercignani: A sketch of the theory of the Boltzmann equation -- O.E. Lanford: Qualitative and statistical theory of dissipative systems -- E.H. Lieb: many particle Coulomb systems -- B. Tirozzi: Report on renormalization group -- A. Wehrl: Basic properties of entropy in quantum mechanics.
Keywords: Mathematics; Differentiable dynamical systems; Materials; Mathematics; Dynamical Systems and Ergodic Theory; Continuum Mechanics and Mechanics of Materials